Me. will give brainliest simplify 12(a - b). 12ab 12a - b 12a - 12b

Skip to content# Me. will give brainliest simplify 12(a – b). 12ab 12a – b 12a – 12b

##
This Post Has 4 Comments

### Leave a Reply

Me. will give brainliest simplify 12(a - b). 12ab 12a - b 12a - 12b

12(A - B)distribute the 12 thru the parenthesisthis means multiply 12 by everything in the parenthesis

(12 * A) - (12 * B) = 12A - 12B <==

12A-12B as we need to multiply everything inside the brackets by 12.

I believe it is 12A - 12B. I apologize in advance if I´m wrong.

Use distributive property: a(b - c) = ab - ac

12(A - B) = 12A - 12B